A methodology to classify interventions in ports demand series changes applied to Brazilian ports. (19th March 2021) - Silva, Francisco Gildemir Ferreira Da; Filho, José Kleber Duarte Macambira
The institutional, commercial and economic structure in Brazil has changed. The Brazilian ports have followed changes by government intervention or exogenous interruption in operation or infrastructure, impacting in the dynamics of port demands. The economical series follow tendencies, interrupted by external or intended interventions and computed by empirical approaches measuring the breakpoint or magnitude of interruption in the series. Methodologically, to classify the intervention is an important deal to decision-makers, contributing to select and use dummy variables in the estimation procedure to better model demand and simulate consequences of some politics of increase infrastructure or protect the retro area of the port. This paper aims to apply the intervention impacts technique to classify then. We use the monthly time series of containers demand for Brazilian ports from 2005 to 2011. As result, we have mapped and showed which types of exogenous interruptions have a significant change in ports movement.